2022
DOI: 10.3389/fphar.2022.949566
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs in anti-cancer drug resistance of non-small cell lung cancer: Recent advances and future potential

Abstract: Non-small cell lung cancer (NSCLC) is one of the most common malignant tumors worldwide. Clinical success is suboptimal owing to late diagnosis, limited treatment options, high recurrence rates, and the development of drug resistance. MicroRNAs (miRNAs), a range of small endogenous non-coding RNAs that are 22 nucleotides in length, have emerged as one of the most important players in cancer initiation and progression in recent decades. Current evidence has revealed the pivotal roles of miRNAs in regulating cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 158 publications
(167 reference statements)
0
9
0
Order By: Relevance
“…The deregulation of miRNA machinery is linked to the acquisition of cancer hallmarks that lead to genome instability and impact on tumor growth, invasion and metastatization ( 82 ). Recent findings have shown that miRNAs could modulate as post-transcriptional regulators the response to EGFR TKIs in overcoming resistance in NSCLC patients, as summarized in Table 2 ( 92 , 93 ). The first evidence of this derived from Hashida S and colleagues’ work, whom investigated the EGFR-TKI resistance mechanisms in a total of 10 afatinib-resistant cell lines from parental NSCLC cells with activating EGFR mutations ( 83 ).…”
Section: Role Of Mirna In Egfr-tki Resistance-brief Overviewmentioning
confidence: 99%
“…The deregulation of miRNA machinery is linked to the acquisition of cancer hallmarks that lead to genome instability and impact on tumor growth, invasion and metastatization ( 82 ). Recent findings have shown that miRNAs could modulate as post-transcriptional regulators the response to EGFR TKIs in overcoming resistance in NSCLC patients, as summarized in Table 2 ( 92 , 93 ). The first evidence of this derived from Hashida S and colleagues’ work, whom investigated the EGFR-TKI resistance mechanisms in a total of 10 afatinib-resistant cell lines from parental NSCLC cells with activating EGFR mutations ( 83 ).…”
Section: Role Of Mirna In Egfr-tki Resistance-brief Overviewmentioning
confidence: 99%
“…The first-generation EGFR-TKIs, such as gefitinib and erlotinib, play a crucial role in the management of LC. However, it is imperative to acknowledge the emergence of resistance to these agents [ 73 ]. Numerous studies have demonstrated the involvement of miRNAs in the development of this resistance.…”
Section: Mirnas In Lcmentioning
confidence: 99%
“…In particular, immunotherapy employing anti-PD-1 or anti-PD-L1 antibodies has emerged as a prominent therapeutic approach for individuals afflicted with advanced NSCLC and SCLC [ 83 , 84 , 85 , 86 ]. In spite of notable clinical advancements, a majority of patients experience suboptimal responses to ICI therapy due to the emergence of primary or secondary resistance [ 73 ].…”
Section: Mirnas In Lcmentioning
confidence: 99%
“…LncRNAs have a variety of roles in biology, including cell-cycle progression, apoptosis, and genomic stability [ 6 ]. Similarly, miRNAs, which typically range from 19 to 25 nucleotides in size, play various roles in biological systems, including their involvement in tumor formation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%